2005
DOI: 10.1086/427513
|View full text |Cite
|
Sign up to set email alerts
|

Immune Reconstitution and Clearance of Human Adenovirus Viremia in Pediatric Stem‐Cell Recipients

Abstract: Lymphocyte reconstitution appears to play a crucial role in clearance of HAdV viremia and survival of the host, warranting further development of therapeutic interventions aimed at improving immune recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
140
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 52 publications
7
140
2
Order By: Relevance
“…21 Data obtained in ORD/MUD SCT recipients from our retrospective study indicated that patients with a low T-cell count (either CD4 þ or CD8 þ T cells) after SCT are at risk of developing an HAdV infection. In our prospective study, 5 children with viraemia only survived the infection if lymphocyte numbers increased to above 0.3 Â 10 9 /l in the period of 4 weeks following the first detection of a positive RQ-PCR. An increase of lymphocyte numbers was clearly associated with a decrease of the plasma DNA load.…”
Section: Immunity and Hadv Infectionmentioning
confidence: 87%
See 2 more Smart Citations
“…21 Data obtained in ORD/MUD SCT recipients from our retrospective study indicated that patients with a low T-cell count (either CD4 þ or CD8 þ T cells) after SCT are at risk of developing an HAdV infection. In our prospective study, 5 children with viraemia only survived the infection if lymphocyte numbers increased to above 0.3 Â 10 9 /l in the period of 4 weeks following the first detection of a positive RQ-PCR. An increase of lymphocyte numbers was clearly associated with a decrease of the plasma DNA load.…”
Section: Immunity and Hadv Infectionmentioning
confidence: 87%
“…When infection progressed to viraemia, defined as the presence of an HAdV DNA load of X1000 copies/ml in two consecutive samples, the time point of first detection of DNA in plasma is usually very close to that of the first positive culture. 5 Importantly, in most patients, a time window of several weeks was observed between the first detection of a significant HAdV DNA load in plasma and the terminal stage of HAdV disease, offering opportunity for intervention. Recently, Lion et al 8 reported that detection of HAdV DNA in whole blood samples is associated with disseminated HAdV disease, which eventually may have a fatal course.…”
Section: Monitoring the Occurrence And Course Of Hadv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Rather commonly, immunosuppressive treatment has been reduced, as reconstitution of the lymphocytic immune system is associated with viral clearance. [13][14][15] AdV-specific T cells have been detected in children after HSCT and seem to protect against AdV disease. 16 For this reason, immunotherapy with donor T cells has been suggested, and a novel approach using purified AdV-specific donor T cells is promising, although in need of further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…adenovirus infection has been correlated with the lack of endogenous T-cell immunity, capable of controlling such infectious agents (Chakrabarti et al, 2002;Feuchtinger et al, 2005;Heemskerk et al, 2005). Current antiviral agents are often limited by weak activity against adenovirus and by side effects, including suppression of bone-marrow function and renal toxicity (Bordigoni et al, 2001;Gavin & Katz, 2002;Ljungman et al, 2003;Lankester et al, 2004;Leruez-Ville et al, 2004).…”
mentioning
confidence: 99%